Pendampingan Santri Kelas 1 Tsanawiyyah Ponpes Assunniyyah dalam Pengenalan I’rab (Kitab I’anah At Thullab) - Ghofur, M Abdul; Islamiyyah, Dina Ulya (An-Nuqthah, 2023)
In the science of nahwu there is i'rob material which studies about changes in the end of sentences caused by differences in the incoming amil. This i'rob material can be used as a benchmark to know the position and meaning of words in Arabic. The purpose of this service is to provide assistance to As-Sunniyyah students in the introduction of I'rob material. The method used to achieve the expected output is divided into three elements, namely: preparation for implementation and evaluation. The results of this assistance by looking at the I'rob term test average: 87, the average I'rob signs test: 93, the average I'rob analysis test: 86 out of 21 students who have carried out the test. The assistance that has been done to the first grade students of Tsanawiyyah in recognizing the I'rob material has been successful and can be continued for a longer period of time.